Analisis peran pembiayaan BMT Syariah Al-Azhaar terhadap peningkatan kesejahteraan anggota perspektif Maqashid Syariah - Rahmat Imanto; Maftukhatusolikhah Maftukhatusolikhah; Ulil Amri (Jurnal Paradigma Ekonomika, 2021)
This study aimed to analyze the role of financing products at BMT Syariah Al-Azhaar Lubuklinggau city, which was rolled out to members and customers of BMT Syariah in improving customer welfare. This study uses a descriptive qualitative method with a case study approach at BMT Syariah Al-Azhaar, Lubuklinggau City, as a research object. The sample used in this study is the customers/members of BMT Syariah Al-Azhaar who get financing products. The data collection of this research used an in-depth interview method. The data obtained were then analyzed using descriptive analysis. The results of this study are BMT Syariah Al-Azhaar, through financing, plays a significant role in improving the welfare of its members. Interest is measured using five indicators of the maintenance of basic needs based on the objectives of maqashid sharia, namely the care of religion, the maintenance of the soul, the maintenance of the mind, the maintenance of offspring, and the maintenance of a property. The increase in welfare experienced by members varies. In general, there is an increase in welfare as measured by the five indicators.